The Influence Of Health Promotion Media On Mother's Behavior In Handling Malnutrition In Children In Bima City - Zahratul Hayati; Ratu Julianti; Uswatun Hasanah (Jurnal EduHealth, 2025)
Malnutrition is a significant health issue in Indonesia, particularly among children. Health promotion media can play an important role in increasing awareness and influencing maternal behavior in addressing malnutrition. This study aims to analyze the influence of health promotion media on maternal behavior in handling malnutrition in children in Bima City. The research uses a quantitative method with a cross-sectional design. The sample consists of 86 mothers with children aged 0-5 years. The independent variables are health promotion media (television, radio, and social media), while the dependent variable is maternal behavior in handling malnutrition. Data were collected using questionnaires and analyzed using descriptive and inferential statistics. The results indicate that: Health promotion media significantly influence mothers' knowledge of malnutrition (p=0.001). Health promotion media affect maternal behavior in providing balanced meals (p=0.01). Social media is the most effective health promotion media in raising mothers' awareness of malnutrition (p=0.05). The conclusion of this study is that health promotion media have a significant influence on maternal behavior in handling malnutrition in children. Therefore, efforts should be made to improve the quality and quantity of health promotion media in Bima City. Based on the study, it is recommended that the government increase the budget for health promotion media, involve the community in developing health promotion media, and conduct further research to develop more effective health promotion media strategies.